PERSEPSI MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG ANGKATAN 2020 DAN 2021 FKIP UNIVERSITAS RIAU TERHADAP PENGGUNAAN MEDIA SOSIAL YOUTUBE SEBAGAI SARANA PEMBELAJARAN BAHASA JEPANG MANDIRI - Ervina Br. Simangunsong; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to determine students perception of Japanese language education study program class of 2020 and 2021 FKIP Riau University towards the use of youtube social media as a means of independent Japanese learning. The research method used is a descriptive quantitative. The sampel of this research were to students class of 2020 and 2021 totaling people and the data obnaited were 53 students, the data was obnaited through a questionnaire distributed through gform. Best on the result of research that has been conducted by researches, it is can be concluded that youtube can be used as a means of independent Japanese language learning because based on the accessibility aspect, are students can access youtube through their cellphone and laptops, then on the usability aspect, youtube provides various Japanese language learning video based learning resourch, and practicality, youtube makes it easy to find the latest information on Japanese language learning, and youtube can also be used anytime and anywhere.Keywords: Youtube Social Media, Learning Media, Japanese Language, Perception